Activities of Institutions of Russian Red Cross Society in Tobolsk Province during Russo-Japanese War: Materials of Newspaper ‘Sibirskiy Listok’ - T. A. Kropotova; M. D. Kiryanova (Научный диалог)
The activities of the institutions of the Russian Red Cross Society in Tobolsk Province during the Russo-Japanese War are presented. The source of the study is a regional periodical publication — the newspaper ‘Sibirskiy Listok’. Publications such as appeals, appeals, notifications, reports, telegrams, and others for the period 1904-1905 (a total of 202 newspaper issues) are examined. It is revealed that the beginning of the Russo-Japanese War contributed to the establishment of the Tobolsk Red Cross Administration and the development of the Tobolsk community of mercy sisters. The extensive materials studied allow us to conclude that the local branch of the Red Cross fully developed during the years of the war. The Ladies’ Committees served as management and organizational structures. The main activity, providing medical assistance, was carried out by the community of mercy sisters. The key directions of the activities of the Tobolsk branch of the Russian Red Cross Society during the Russo-Japanese War were the establishment and maintenance of the community of mercy sisters, the creation of a stage hospital, and the provision of all necessary support to the wounded. For this purpose, donations were collected from the population. Analysis of publications in ‘Sibirskiy Listok’ showed a high degree of activity of the province’s population in the activities of the Tobolsk branch of the Russian Red Cross Society.